Hubungan Tingkat Pendidikan dan Pendapatan Orang Tua Terhadap Status Gizi Anak: Literature Review - Olivia Sianturi; Siti Rahayu Nadhiroh; Qonita Rachmah (Universitas Airlangga, 2023)
Background: Monitoring children's nutritional status is one of the factors that create qualified human resources. Children aged 0-59 months who are malnourished will experience growth disorder if not taken seriously. Several factors that associated with nutritional status of children are parent's educational level and income. Objectives: The purpose of this literature review was to analyze the relationship between parent's educational level and income on child's nutrition status. Methods: This article is a literature review based on articles that was published within the last ten years. Electronic databases like PubMed and Google Scholar were used. There are 17 literatures that used in this article. Discussion: Some articles show that child's nutritional status is related to the parents' income and education level. Educated parents are able to explain the nutritional value of food and comprehend more about the physical and mental development of their children. The availability of food and efforts to provide a balanced diet are influenced by parental income, and this will have an impact on the nutritional health of children. Nevertheless, there are still many factors that can affect the nutritional status of children. Conclusions: Parents' education level and income was not significantly associated with children's nutritional status. This due to the development of information technology and human resources